1996
DOI: 10.1161/01.cir.94.6.1298
|View full text |Cite
|
Sign up to set email alerts
|

Defective l -Arginine–Nitric Oxide Pathway in Offspring of Essential Hypertensive Patients

Abstract: Offspring of essential hypertensive patients are characterized by a reduced response to acetylcholine linked to a defect in the nitric oxide pathway, suggesting that an impairment in nitric oxide production precedes the onset of essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
164
3
11

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(190 citation statements)
references
References 36 publications
12
164
3
11
Order By: Relevance
“…nitrites and nitrates and the NO inactivating factor namely plasma hemoglobin, present freely in plasma. Essential hypertension is characterized by impaired endotheliumdependent vasodilation [29]. In our study nitrite and nitrate values were similar in controls of both age groups slightly higher in the higher age group controls (Group II).…”
Section: Resultssupporting
confidence: 59%
“…nitrites and nitrates and the NO inactivating factor namely plasma hemoglobin, present freely in plasma. Essential hypertension is characterized by impaired endotheliumdependent vasodilation [29]. In our study nitrite and nitrate values were similar in controls of both age groups slightly higher in the higher age group controls (Group II).…”
Section: Resultssupporting
confidence: 59%
“…Several lines of evidence have suggested that endothelial function is impaired as blood pressure increases and that the degree of dysfunction is related to the magnitude of blood pressure elevation, 64,65 indicating that endothelial dysfunction is a consequence of hypertension. In contrast, Taddei et al 66 recently presented interesting results showing that young offspring of essential hypertensive patients who have a family history of hypertension are characterized by a reduced response to acetylcholine linked to a defect in the NO pathway, suggesting that endothelial dysfunction may be a cause of hypertension. There is still insufficient evidence for a conclusion to be reached.…”
Section: Endothelial Dysfunction and Hypertensionmentioning
confidence: 94%
“…They demonstrated attenuated responses to endothelium depen-dent vasodilators such as acetylcholine but preserved responses to endothelium independent vasodilators such as sodium nitroprusside in hypertensive patients 31,32 and even in their normotensive offspring. 33 However, not all human trials have confirmed these abnormalities of vascular NO bioactivity in hypertension. Cockroft et al 34 studied endothelial function in a larger population of essential hypertensives than previous trials and found vasodilator responses to muscarinic agonists and nitroprusside to be similar to those in normotensive controls.…”
Section: Endothelial No and Hypertensionmentioning
confidence: 99%